Impact of e-sport games on the character building and sports culture - Sigit Nugroho; Sumarjo Sumarjo; Ahmad Nasrulloh; Kukuh Wahyudin Pratama (Jurnal Keolahragaan, 2022)
E-Sport games are examples of a game that is played without engaging in any physical activity. The objective of the research is to determine the impact of e-Sport games on character building and sports culture. This research utilized mixed methods. The researchers were using questionnaires to collect the quantitative data and they used qualitative data triangulation to collect the qualitative data. The students and lecturers of the Faculty of Sports Science, Yogyakarta State University comprised the research population. The convenience sampling technique was used to select the 35 students, while the lecturers and trainers used the purposive sampling with a total of 5 people. The quantitative research instrument consisted of a modified Likert scale questionnaire and the qualitative research instrument consisted of the researcher himself assisted by a list of themes. The researchers used Miles and Huberman’s quantitative data analysis techniques with descriptive percentage and qualitative analysis techniques for the data analysis. The findings of the research on e-Sport games have an impact on the formation of positive and negative characters. The impact of positive characters includes honesty, responsibility, cooperation, and courtesy and the impact of negative characters is depression, stress, and anxiety. While the influence of e-Sport games in sports culture includes hard work, discipline, respect, and competition. The positive impact of e-Sport games is in the very good category, with the highest factor being honesty (100%). The negative impact is in the moderate category, with the highest factor being depression (52.5%). While the e-Sport game on sports culture is in the very good category, with the highest influence is on hard work (95%). This research can be concluded that e-Sport games have a very good impact on character building and sports culture.